A brief history of seven killings - James, Marlon, 1970- (Oneworld, 2014)
"From the acclaimed writer of The Book of Night Women comes a masterful novel framed as a fictional oral history that explores the events and characters surrounding the attempted assassination of Bob Marley during the political turmoil on Jamaica in the late 1970s"--